Co‐producing knowledge: the Integrated Ecosystem Model for resource management in Arctic Alaska. Issue 8 (27th February 2020) - Euskirchen, Eugénie S; Timm, Kristin; Breen, Amy L; Gray, Stephen; Rupp, T Scott; Martin, Philip; Reynolds, Joel H; Sesser, Amanda; Murphy, Karen; Littell, Jeremy S; Bennett, Alec; Bolton, W Robert; et al.
Abstract : Assessments of climate‐change effects on ecosystem processes and services in high‐latitude regions are hindered by a lack of decision‐support tools capable of forecasting possible future landscapes. We describe a collaborative effort to develop and apply the Integrated Ecosystem Model (IEM) for Alaska and northwestern Canada to explore how climate change influences interactions among disturbance regimes, permafrost integrity, hydrology, and vegetation, and how these dynamics in turn influence resource management decisions. This process emphasizes co‐production of knowledge among decision makers, scientists, major funders, partners, and stakeholders. We highlight research findings based on IEM applications in Arctic Alaska, as well as successes and challenges of the co‐production process. The overall framework and lessons from our work with the IEM are relevant to other collaborative efforts outside the Arctic that aim to develop a decision‐support tool or an undertaking of equivalent scope.